A rapid spectrophotometric method to resolve a binary mixture of food colorants (riboflavine and sunset yellow) - Özgür, MÜ (Tubitak Scientific & Technological Research Council Turkey, 2004)
A very simple and rapid spectrophotometric method using measurements at zero-crossing wavelength is described for resolving binary mixtures of riboflavine (E-101) and sunset yellow (E-110) in a powder drink. The assay procedure for E-110 and E-101 involves the extraction of the colorants from the powder drink with pH 4.5 acetate buffer, filtration, appropriate dilution, and measurement of the first derivative absorbance values (denoted as D-1). Calibration graphs are linear tip to 25.0 mug.mL(-1) for E-101 and 40.0 mug.mL(-1) for E-110. The sensitivity and reproducibility of the method were determined by using the synthetic mixtures in different ratios prepared by us, and the proposed method was applied to a commercially available powder drink. The relative standard deviations obtained are 1.39% and 1.15% and the average percentage recoveries are 101.0% and 102.8% for E-101 and E-110, respectively.
Keywords: derivative spectrophotometry; simultaneous determination; zero-crossing measurements; sunset yellow; riboflavine; colorants; food analysis; PARTIAL LEAST-SQUARES; ION-PAIR FORMATION; QUINOLINE YELLOW; BIVARIATE CALIBRATION; PONCEAU 4R; MULTIVARIATE CALIBRATION; ACETYLSALICYLIC-ACID; COMMERCIAL PRODUCTS; TERNARY MIXTURES; Chemistry; Engineering